2023
DOI: 10.1002/hsr2.1555
|View full text |Cite
|
Sign up to set email alerts
|

A clinician's guide to gallstones and common bile duct (CBD): A study protocol for a systematic review and evidence‐based recommendations

Vahid Sebghatollahi,
Mohammadreza Parsa,
Mohammad Minakari
et al.

Abstract: Background and AimsGallstones are one of the most common and costly diseases of the gastrointestinal tract and occur when a combination of deposits consisting of fat or minerals accumulate in the gallbladder or common bile duct (CBD). This paper provides a comprehensive review of gallstone epidemiology, diagnosis, and management, focusing on current clinical guidelines and evidence‐based approaches.MethodsA systematic literature review gathered information from various sources, including PubMed, Trip, Google S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
22

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 36 publications
0
4
0
22
Order By: Relevance
“…The accuracy of transabdominal ultrasound in detecting gallstones is more than 95% (32). In this study, high SII score was found to be positively associated with gallstones risk in people under 50 years of age.…”
Section: Discussionmentioning
confidence: 51%
“…The accuracy of transabdominal ultrasound in detecting gallstones is more than 95% (32). In this study, high SII score was found to be positively associated with gallstones risk in people under 50 years of age.…”
Section: Discussionmentioning
confidence: 51%
“…In recent years, the global incidence of gallbladder stones has seen a notable increase, attributed largely to dietary changes and improvements in quality of life [ 1 , 6 , 7 ]. Concurrently, the prevalence of choledocholithiasis, especially in the postoperative phase, has become a point of concern [ 1 ]. Our case highlights a patient who, following a seemingly successful LC, presented with symptoms indicative of bile duct obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…In the realm of gallstone disease management, the post-cholecystectomy period poses unique challenges, particularly with the occurrence of hidden bile duct stones [ 1 ]. Despite the widespread adoption of laparoscopic cholecystectomy (LC) for its minimally invasive benefits, patients can still face significant postoperative complications, such as choledocholithiasis [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Серед пацієнтів із симптоматичною ЖКХ від 10% до 20% мають ХДЛ. До 15% хворих на ЖКХ мають ХДЛ, і майже у 10% ХДЛ не виявляється до операції [1,2,3,4,9,12,13,14,15,21,27,28,29,30].…”
Section: Discussion Of Epidemiological Clinical Diagnostic Aspects An...unclassified